AKTA KELAHIRAN TERHADAP ANAK YANG DILAHIRKAN DI LUAR PERKAWINAN - Gresky Gistor Mangayuk (Universitas 17 Agustus 1945 Samarinda, 2022)
ABSTRACTBirth registration is an important matter in population registration and administration, and so far this problem has received little attention in the community. Given the importance of this birth certificate, a child must have a birth certificate even though he is a child out of wedlock, this is because the birth certificate is an authentic certificate that will be used as evidence regarding the child's civil status. In this study, the author uses a descriptive type of research, which is a study that is intended to provide an overview of the state of the subject and/or object of research as it is. The results of this study indicate that the process of obtaining a birth certificate for a child out of wedlock is the same in general as for a legitimate child, except that the mother must first fill out a statement that she is not legally married at the population service and the civil registry signed by the head of the population and civil registry office. one of the requirements in obtaining a birth certificate of a child out of wedlock. In the validity of the birth certificate of a child out of wedlock, it can be shown through a quote in the deed that has been issued by the population and civil registry office and also signed by the head of the population and civil registry office, which means that the validity of the deed of a child out of wedlock is the same as that of a legitimate child. can be used as authentic evidence for the certificate holder, with a birth certificate a person has legal guarantees and certainty regarding his civil status which includes personal identity, namely, name, place, and date of birth, and citizenship. Constraints in obtaining birth certificates for children out of wedlock can be seen from 2 (two) sides, namely the community and the apparatus including the lack of public awareness of the importance of birth certificates for children and also the lack of active role of civil registration officers to inform the importance of birth certificates for children in the future. the future, whether it's a child born out of wedlock. Keywords: Out of wedlock children, birth certificate, legal consequences